关于国有企业激励与约束机制的探讨 = Incentives and regulations in state-owned enterprises - 王少坤 Wang, Shaokun (2008)
Based on the theory of asymmetric information and relevant literature on "adverse selection" and "moral hazard", this thesis explores in details the causes of "Fifty-Nine Years Old Phenomena " and "Black Hole Phenomena" in the process of reforming the state-owned sector. With an official survey result at the national level and an investigation conducted in Dezhou City, the basic principles and measures of a new system of selection, incentives and monitoring which are market-oriented are discussed. The thesis argues that the new system of selection, incentives and monitoring should be able to make SOEs more independent and accountable.